PENCEGAHAN TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) - Syahrullah (Legalita, 2020)
This study discusses the efforts of the Lampung Regional Police in preventing criminal acts of trafficking in persons (trafficking law). Study on Ditreskrimsus Polda Lampung Optimal or professional law enforcement, especially regarding how to deal with it. Because prevention efforts are essentially an integral part of the welfare and protection of the community. Meanwhile, prevention efforts, whether criminal acts, are not easy or impossible to eliminate as imagined, whether it is protection of individuals, society or the state. As we know that the ultimate goal or main goal of criminal politics or policy is about the repetition of crimes. Based on the formulation of the problem discussed by the author, it can be concluded that: The efforts of the Lampung Police in preventing human trafficking are carried out through steps, namely pre-emptive efforts including conveying it to mosque congregations, assigning Bhabinkamtibmas and conducting legal counseling, While preventive efforts are carried out by patrolling, coordinating with kelurahan, RT/RW and religious leaders, deploying teams, establishing guard posts and conducting mapping, while repressive efforts are carried out by seeking information through investigations, undercovers and conducting operations. Suggestions that the author can convey based on the results of this research are: Lampung Regional Police members should often patrol this to prevent or narrow down criminal acts that occur in the community as well as be used as an approach to the community to find out the security situation and any complaints that occur in the community.